Sosiologi Pendidikan Dalam Pemikiran Ibnu Khaldun - Hendra, Djaja (JURNAL PENDIDIKAN, 2021)
Abstract: The thinkers assume that the 'Father of Sociology' must be Auguste Comte (France). Whereas about 4 centuries ago, before Comte was born, the behavior of the people had been discussed by Ibn Khaldun (Islamic Sociologist). At that time the term sociology was not yet known, let alone talking about the sociology of education. Sociology of education is deliberately displayed and tries to be explored and sought in the main points of Ibn Khaldun's thoughts when he is talking about people's behavior in his work entitled Mukaddinah. In the book, indeed, Ibn Khaldun does not talk specifically about the sociology of education, but we ourselves are trying to find the scattered fragments according to our field of knowledge in his work. The advantages of Ibn Kahdun when talking about the behavior of society as a whole, then where do we look for the sociology of education? Also, what should not be forgotten is that Ibn Khaldun also includes his teaching methods. Why is that? Ibn Khaldun is a thinker as well as someone who compares with the reality on the ground. This can happen because he is a thinker who is behind the desk as well as being in the government (demands field work). He theorizes as well as application.  Keywords: sociology of education, main ideas, community behavior